The Effect of Price and Consumer Interest in Boba Drinks in Indonesia: A Case Study of Capcin Idano in the City of Sukabumi - Mintawati, Hesri; Desianti, Lisa Chandrasari; Aulia, Tasya; Risa, Risa; Vinoza, Ridan Ahwi (JUDICIOUS, 2024)
Boba beverages have become a popular trend in Indonesia, with a variety of boba drinks available in the market. This research aims to understand how price and consumer interest influence people's inclination to purchase boba drinks, focusing on Capcin Idano in Sukabumi City. We utilized a qualitative method, conducting interviews with Capcin Idano consumers and performing a literature review. The findings indicate that affordable pricing and high consumer interest play significant roles in influencing consumers' purchasing decisions regarding Capcin Idano boba drinks. This study provides insights into the factors affecting consumer interest in boba beverages, which can be valuable for the beverage industry and future researchers.